Erythropoietin Improved Cognitive Function and Decreased Hippocampal Caspase Activity in Rat Pups after Traumatic Brain Injury - Schober, Michelle E. (Mary Ann Liebert, Inc., 2014)
Traumatic brain injury (TBI) is a leading cause of acquired neurologic disability in children. Erythropoietin (EPO), an anti-apoptotic cytokine, improved cognitive outcome in adult rats after TBI. To our knowledge, EPO has not been studied in a developmental TBI model. Hypothesis: We hypothesized that EPO would improve cognitive outcome and increase neuron fraction in the hippocampus in 17-day-old (P17) rat pups after controlled cortical impact (CCI). Methods: EPO or vehicle was given at 1, 24, and 48 h after CCI and at post injury day (PID) 7. Cognitive outcome at PID14 was assessed using Novel Object Recognition (NOR). Hippocampal EPO levels, caspase activity, and mRNA levels of the apoptosis factors Bcl2, Bax, Bcl-xL, and Bad were measured during the first 14 days after injury. Neuron fraction and caspase activation in CA1, CA3, and DG were studied at PID2. Results: EPO normalized recognition memory after CCI. EPO blunted the increased hippocampal caspase activity induced by CCI at PID1, but not at PID2. EPO increased neuron fraction in CA3 at PID2. Brain levels of exogenous EPO appeared low relative to endogenous. Timing of EPO administration was associated with temporal changes in hippocampal mRNA levels of EPO and pro-apoptotic factors. Conclusion/Speculation: EPO improved recognition memory, increased regional hippocampal neuron fraction, and decreased caspase activity in P17 rats after CCI. We speculate that EPO improved cognitive outcome in rat pups after CCI as a result of improved neuronal survival via inhibition of caspase-dependent apoptosis early after injury.